(untitled) (Edma 0-6: Educación Matemática en la Infancia, 2024)
When we deal with argumentative competence in class there are many points of view: teacher’s and student’s point of view and the external point of view of knowledge (in a theoretical sense). The research shows a qualitative experimental study that allows a comparison between different perspectives in order to measure argumentative competence. The study involved 5 classes and 9 teachers. First, the idea of argumentative competence was discussed from a theoretical and institutional point of view in the Italian school system. Then questionnaires were administered to teachers and deep interviews were conducted with students. Finally, teachers participated in focus groups, and this allowed reflections and encouraged discussion. The process implemented allowed an in-depth key on the concept of argumentative competence. Also, the analysis of the results of the questionnaire and interviews shows how classroom practices are related to teacher and students’ attitudes and beliefs in mathematics.